Redoxins in peripheral neurons after sciatic nerve injury - Valek, Lucie; Kanngießer, Maike; Häussler, Annett; Agarwal, Nitin; Lillig, Christopher Horst; Tegeder, Irmgard (Free radical biology and medicine, 2015)
Peripheral nerve injury causes redox stress in injured neurons by upregulations of pro-oxidative enzymes, but most neurons survive suggesting an activation of endogenous defense against the imbalance. As potential candidates we assessed thioredoxin-fold proteins, called redoxins, which maintain redox homeostasis by reduction of hydrogen peroxide or protein dithiol-disulfide exchange. Using a histologic approach, we show that the peroxiredoxins (Prdx1-6), the glutaredoxins (Glrx1, 2, 3 and 5), thioredoxin (Txn1 and 2) and their reductases (Txnrd1 and 2) are expressed in neurons, glial and/or vascular cells of the dorsal root ganglia (DRGs) and in the spinal cord. They show distinct cellular and subcellular locations in agreement with the GO terms for “cellular component”. The expression and localization of Glrx, Txn and Txnrd proteins was not affected by sciatic nerve injury but peroxiredoxins were upregulated in the DRGs, Prdx1 and Prdx6 mainly in non-neuronal cells and Prdx4 and Prdx5 in DRG neurons, the latter associated with an increase of respective mRNAs and protein accumulation in peripheral and/or central fibers. The upregulation of Prdx4 and Prdx5 in DRG neurons was reduced in mice with a cre-loxP mediated deficiency of hypoxia inducible factor 1 alpha (HIF1α) in these neurons. The results identify Prdx4 and Prdx5 as endogenous HIF1α-dependent, transcriptionally regulated defenders of nerve injury evoked redox stress that may be important for neuronal survival and regeneration.
Gesehen am 07.07.2020